Biarkanlah Perempuan dengan HIV/AIDS Berbicara! Teologi Interkultural Feminis Poskolonial dalam Ketidakadilan Gender - Paulus Eko Kristianto (UIN Sunan Gunung Djati Bandung, 2021)
This article discusses feminist intercultural theological (mission) models in the context of gender injustice experienced by women living with HIV/AIDS. Through library research, the authors find that the right model is to provide space for those who talk integrated with service. Service is not only for God, but for each other in a concrete way, including realizing gender justice for women with HIV/AIDS.